2018
DOI: 10.1177/0269216318779238
|View full text |Cite
|
Sign up to set email alerts
|

Ambulance staff and end-of-life hospital admissions: A qualitative interview study

Abstract: Background:Hospital admissions for end-of-life patients, particularly those who die shortly after being admitted, are recognised to be an international policy problem. How patients come to be transferred to hospital for care, and the central role of decisions made by ambulance staff in facilitating transfer, are under-explored.Aim:To understand the role of ambulance staff in the admission to hospital of patients close to the end of life.Design:Qualitative interviews, using particular patient cases as a basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(95 citation statements)
references
References 33 publications
4
87
0
4
Order By: Relevance
“…Data were synthesised to understand both the individual case-patients’ admission, and the admissions collectively, with synthesis aided by reference to both end-of-life care and sociological literature. Extended details about the study methodology26 , 27 and related findings10 can be found elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Data were synthesised to understand both the individual case-patients’ admission, and the admissions collectively, with synthesis aided by reference to both end-of-life care and sociological literature. Extended details about the study methodology26 , 27 and related findings10 can be found elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Few papers focused on family and significant others’ experiences, but those that did reported the lasting impact of these events. 61 68 70 77 83 84 Included papers reported on family experiences in prehospital palliative and EoLC, 61 68 83 OHCA, 70 77 resuscitation 76 and suicide. 84 Witnessing a family member die or dying was reported as having a significant effect on relatives and particularly at OHCAs, families experienced a range of emotions, including reactions of shock, vulnerability, responsibility and hopelessness.…”
Section: Resultsmentioning
confidence: 99%
“…Papers that included family members’ accounts and experiences were few and tended to focus on their interactions with HCPs, including communication and behaviours during resuscitation and cardiac events, 70 76 77 EoLC, 61 68 83 the impact of cardiac events 70 77 88 and occasionally experiences of suicide. 84 Generally, relatives reported positive interactions with PHPs, commenting on their confidence and calmness in attending scenes involving death and dying, and while some families reported more negative encounters, it suggests there may be a disconnect between PHPs’ perceptions of the care they provide and families’ experience of that care.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to non-conveyance of palliative care patients to hospital have been shown to include the lack of out-of-hours cover by palliative care specialists,2 difficulties arranging care particularly out of hours, limited available patient information and service emphasis on emergency care 3. One study showed that lack of access to palliative care nurses is a reason for unnecessary admissions of older patients 4…”
Section: Discussionmentioning
confidence: 99%